Sedimentation upon Different Carrier Liquid in Giant Electrorheological Fluid and Its Application - Hong, Yaying; Wen, Weijia (Frontiers in Materials, 2014)
When giant electrorheological (GER) fluid is settled after some time, particles can precipitate out of the oil in a multistep process that involves the formation of larger particles, the aggregation of colloids, and eventual sedimentation. Colloidal stability in giant electrorheological (GER) fluid can influence the GER performance and the fluid flow steadiness. We investigated the sedimentation effect of the GER particles suspended in various carrier liquid. Different from the existing electrorheological (ER) fluids, GER particles consisting of oxalate core with urea coating are found oil synergistic. The sedimentation effect of the particles suspended in oils from the family of synthetic oil and mineral oil were checked by direct observation. The rheological behavior of the GER fluid upon electric field application was also investigated. These experiments showed that stable colloidal suspension and good GER effect can be achieved coherently by favorable particle-oil interaction. The resultant high yield stress and low sedimentation rate achieved due to the instrumental linking of hydrogen bond is showed in the hydrogenated silicone oil carrier liquid. With the anti-sedimentation characteristic upon the new carrier oil, hydrogenated silicone oil-GER fluid, we investigated their GER effect in a modified mono tube damper and the experimental result showed wide controllability range. Our investigations may broaden engineering applications.